ANALISIS PENERAPAN AKUNTANSI PADA TOKO OLEH-OLEH MAKANAN KHAS RIAU DI PEKANBARU - Dian Saputra; Dian Tri Ramadhani (UIR Press, 2022)
The study was conducted in the city of Pekanbaru. With regard to this research, the object is a souvenir entrepreneur typical of Riau food (oleh-oleh makanan khas Riau). The problem raised in this study is how the application of accounting carried out by riau food souvenirs in Pekanbaru and its conformity with basic concepts and accounting principles. The purpose of this research is to find out the suitability of the application of accounting carried out by riau food souvenirs in Pekanbaru with basic concepts and accounting principles. There are two types of data used in this study, Primary and Secondary data. The methods of data collection in this study are structured interviews, documentation and observations. While the data analysis technique used is Descriptive analysis. Based on the results of research and discussion that has been outlined, the application of accounting in riau food souvenirs in Pekanbaru has not been in accordance with basic concepts and accounting principles.